Actinomycosis of the parotid masquerading as malignant neoplasm. - Varghese, Bipin T (BioMed Central, 2004)
BACKGROUND: Primary actinomycosis of the parotid gland is of rare occurrence and can mimic a malignant neoplasm both clinically as well as radiologically. CASE PRESENTATION: We present here a case of primary actinomycosis of the parotid gland presenting with a parotid mass lesion with erosion of skull bones. CONCLUSIONS: Clinical presentation of cervico-facial actinomycosis is characterized by the presence of a suppurative or indurative mass with discharging sinuses. The lesion demonstrates characteristic features on fine needle aspiration cytology and histology, however at times the findings are equivocal.